Promising Practices for a Better Tomorrow: A Qualitative Study of Successful Practices in Senior High School Education - Osias Kit T Kilag; Trinidad P Evangelista; John Michael Sasan; Almari M Librea; Rechelle Mary C Zamora; Shannel B Ymas; Nove Anne P Alestre (Research Synergy Foundation, 2023)
This qualitative research study aimed to explore and understand successful approaches used in senior high school education. The study included 12 participants, consisting of 6 teachers and 6 students, who were selected based on their experiences and perspectives related to successful approaches in senior high school education. The study utilized semi-structured interviews for data collection and qualitative content analysis for data analysis. The research revealed four main themes: Collaborative Teaching and Learning, Holistic Support for Students, Innovative Teaching and Learning Approaches, and Emphasis on Student Assessment and Evaluation. These findings provide insights into the experiences and perspectives of teachers and students regarding successful approaches in senior high school education. The study underscores the importance of collaborative teaching and learning, providing holistic support for students, incorporating innovative teaching and learning approaches, and emphasizing student assessment and evaluation to achieve success in senior high school education. These findings have implications for policy and practice in senior high school education and contribute to the ongoing discussion on providing quality education for all students. This study highlights the need for continuous efforts to improve senior high school education and emphasizes the importance of considering the perspectives and experiences of teachers and students in these efforts.